2012
DOI: 10.1002/jsfa.5905
|View full text |Cite
|
Sign up to set email alerts
|

The growth performance of Jade Tiger cultured abalone fed diets supplemented with fish oil and vegetable oils

Abstract: Supplementation with 1.5% of dietary FO can improve growth performance in cultured abalone. It is feasible to replace 75% of dietary FO with FlaxO and 50% of dietary FO with CO, without negative effect on growth performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Limited growth of abalone in all experimental groups, even though for 120-days period, may be related to the absence of dietary ARA and EPA. Similarly, lower growth rate was also observed in abalone fed diets containing lower levels of n-3 LC-PUFA (Mateos et al, 2013). The present study confirmed the contributing effects of EFA (LA and ALA) on growth of abalone in comparison with the group fed diet without EFA supplementation.…”
Section: Discussionsupporting
confidence: 86%
“…Limited growth of abalone in all experimental groups, even though for 120-days period, may be related to the absence of dietary ARA and EPA. Similarly, lower growth rate was also observed in abalone fed diets containing lower levels of n-3 LC-PUFA (Mateos et al, 2013). The present study confirmed the contributing effects of EFA (LA and ALA) on growth of abalone in comparison with the group fed diet without EFA supplementation.…”
Section: Discussionsupporting
confidence: 86%
“…H. tuberculata growth seemed to be highly correlated to n-3 poly-unsaturated fatty acids (PUFA) in algal composition as demonstrated by Mai et al (1996) with a SGR of 1.31 % day -1 when fed a P. palmata diet containing the highest amount of n-3 PUFA (49.7% of total fatty acids) compared to a SGR of 1.03 % day -1 when fed L. saccharina diet containing the lowest n-3 PUFA (25.2% of total fatty acids). A lower SGR (0.30 % day -1 ) was also observed in Jade tiger hybrid abalone fed canola oil diets containing lower levels of n-3 PUFA (12.5% of total fatty acids) compared to a higher SGR (0.47 % day 1 ) when fed fish oil diet containing more n-3 PUFA (27.5 % of total fatty acids) (Mateos et al, 2013). In our experiment, total PUFAs were not related to growth enhancement.…”
Section: Accepted Manuscriptmentioning
confidence: 73%